Adipose-derived stem cells alleviate liver injury induced by type 1 diabetes mellitus by inhibiting mitochondrial stress and attenuating inflammation - Hou, Yanli; Ding, Wenyu; Wu, Peishan; Liu, Changqing; Ding, Lina; Liu, Junjun; Wang, Xiaolei (Stem cell research & therapy, 2022)
Type 1 diabetes mellitus (T1D) is a worldwide health priority due to autoimmune destruction and is associated with an increased risk of multiorgan complications. Among these complications, effective interventions for liver injury, which can progress to liver fibrosis and hepatocellular carcinoma, are lacking. Although stem cell injection has a therapeutic effect on T1D, whether it can cure liver injury and the underlying mechanisms need further investigation. Sprague-Dawley rats with streptozotocin (STZ)-induced T1D were treated with adipose-derived stem cell (ADSC) or PBS via the tail vein formed the ADSC group or STZ group. Body weights and blood glucose levels were examined weekly for 6 weeks. RNA-seq and PCR array were used to detect the difference in gene expression of the livers between groups. In this study, we found that ADSCs injection alleviated hepatic oxidative stress and injury and improved liver function in rats with T1D; potential mechanisms included cytokine activity, energy metabolism and immune regulation were potentially involved, as determined by RNA-seq. Moreover, ADSC treatment altered the fibroblast growth factor 21 (FGF21) and transforming growth factor β (TGF-β) levels in T1D rat livers, implying its repair capacity. Disordered intracellular energy metabolism, which is closely related to mitochondrial stress and dysfunction, was inhibited by ADSC treatment. PCR array and ingenuity pathway analyses suggested that the ADSC-induced suppression of mitochondrial stress is related to decreased necroptosis and apoptosis. Moreover, mitochondria-related alterations caused liver inflammation, resulting in liver injury involving the T lymphocyte-mediated immune response. Overall, these results improve our understanding of the curative effect of ADSCs on T1D complications: ADSCs attenuate liver injury by inhibiting mitochondrial stress (apoptosis and dysfunctional energy metabolism) and alleviating inflammation (inflammasome expression and immune disorder). These results are important for early intervention in liver injury and for delaying the development of liver lesions in patients with T1D.